2017
DOI: 10.1177/1527476417741200
|View full text |Cite
|
Sign up to set email alerts
|

The Spotify Effect: Digital Distribution and Financial Growth

Abstract: This article analyzes Spotify as a media company that operates at the intersection of advertising, technology, music, and finance. In doing so, this article contributes to media industry studies as a field that investigates the relation between various industrial and economic actors. Given that the media industries, as any other industry, can be defined as a set of markets, one of which is the leading market, and to which other markets are auxiliary, the question asked is what market is leading in the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 27 publications
0
40
0
7
Order By: Relevance
“…Music metadata (data that describe and contextualize music) play a role in the production of ‘musical experiences’, as ‘a digital file rarely exists in solitude and is instead accompanied and linked together with other types of data’ (Eriksson, 2016). Crucially, in addition to existing as a sound recording, ‘music has become data, and data in turn has become contextual material for user targeting at scale’ (Vonderau, 2019). Our focus is on the relationship between user data – a sought-after asset that has been likened to oil (Deutscher, 2013; The Economist , 2017) – and platform capital, whose accumulation strategy hinges on controlling this new music industry currency.…”
Section: Music Digital Distribution and Platform Accumulationmentioning
confidence: 99%
“…Music metadata (data that describe and contextualize music) play a role in the production of ‘musical experiences’, as ‘a digital file rarely exists in solitude and is instead accompanied and linked together with other types of data’ (Eriksson, 2016). Crucially, in addition to existing as a sound recording, ‘music has become data, and data in turn has become contextual material for user targeting at scale’ (Vonderau, 2019). Our focus is on the relationship between user data – a sought-after asset that has been likened to oil (Deutscher, 2013; The Economist , 2017) – and platform capital, whose accumulation strategy hinges on controlling this new music industry currency.…”
Section: Music Digital Distribution and Platform Accumulationmentioning
confidence: 99%
“…; see Zhang et al 2013), and why Spotify should collaborate with large big data companies such as Facebook and Twitter so that it can produce richer playlists and more sophisticated recommendations for its listeners (Germain and Chakareski 2013; Pichl, Zangerle, and Specht 2014). Recently, critics have reported that millions of songs on Spotify catalog have not been played (Palermino 2014) and that the platform fails to comply with the EU data protection laws (Eriksson et al 2019; Marshall 2015; Vonderau 2019). However, little has been published regarding the condition of the producers of digital music.…”
Section: Introductionmentioning
confidence: 99%
“…Skeggs and Yuill 2016). Preliminary results of the research are published separately (Vonderau 2017). …”
Section: Journal Of Current Cultural Researchmentioning
confidence: 99%